2006
DOI: 10.1109/tgrs.2006.864391
|View full text |Cite
|
Sign up to set email alerts
|

Land cover classification using fuzzy rules and aggregation of contextual information through evidence theory

Abstract: Land cover classification using multispectral satellite image is a very challenging task with numerous practical applications. We propose a multi-stage classifier that involves fuzzy rule extraction from the training data and then generation of a possibilistic label vector for each pixel using the fuzzy rule base. To exploit the spatial correlation of land cover types we propose four different information aggregation methods which use the possibilistic class label of a pixel and those of its eight spatial neig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 30 publications
0
13
0
1
Order By: Relevance
“…The Dempster's combination rule was used to combine evidences provided by single rules. A work on combining a fuzzy rule-based system with the Dempster-Shafer theory was also reported recently by Laha et al (2006). In this work a single fuzzy rule generated a fuzzy label vector.…”
Section: Ensemble Systems and Dempster's Combination Rulementioning
confidence: 80%
“…The Dempster's combination rule was used to combine evidences provided by single rules. A work on combining a fuzzy rule-based system with the Dempster-Shafer theory was also reported recently by Laha et al (2006). In this work a single fuzzy rule generated a fuzzy label vector.…”
Section: Ensemble Systems and Dempster's Combination Rulementioning
confidence: 80%
“…Furthermore, Lu et al [19] have confirmed the effectiveness and usefulness of fuzzy logic combined with an extension of DS theory in data fusion. In land cover classification, DS theory and fuzzy-contextual information [20] have been used in the classification of multispectral satellite images. This method reduces classification error compared to Markov random field (MRF)-based contextual classification.…”
Section: Introductionmentioning
confidence: 99%
“…Laha et al [23], for instance, applied evidence theory to incorporate contextual information for further image classification using fuzzy rules. Ghimire et al [15] applied random forests, and Stuckens et al [39] employed a linkage-based clustering algorithm for land cover classification using contextual information.…”
Section: Introductionmentioning
confidence: 99%